Productividad de la mano de obra en construcciones civiles utilizando mapa de flujo de valor y carta de balance de cuadrilla - Edwin, Francisco Tello Oquendo (2020)
The productivity calculation in the construction sector is an essential factor in both the economic and organizational fields. Nevertheless, there are few studies on the methodologies that allow calculating productivity effectively. Moreover, the related literature only show a productivity result, but it does not describe the reasons for this result. Therefore, this research analyzes the productivity of the construction workforce. It considers the building process and the work crew settings. The used methodology allows calculating productivity in an integral way for the different areas of construction. The value stream mapping (VSM) and the crew balance charts (BC) were used for this research. In this study, construction items such as reinforcing steel, concrete, masonry and plaster were analyzed. As a result, it is proposed a correlation between the productivity and the percentage of activities that add value to the work (AV), understanding as value the elimination of everything that produces losses in the execution of the activities. The already mentioned correlation establishes the percentage of AV for a productivity measure since the VSM and BC tools allows to determine how the work is being done in the construction item and identifying possible opportunities for productivity improvement. In the analyzed construction items, these opportunities consist of reducing the time spent on activities such as transportation and waiting for materials, cleaning, unscheduled refreshments, lack of activities.